Recent developments in nucleic acid-based therapies for Parkinson’s disease: Current status, clinical potential, and future strategies - Pandey, Shivam Kumar; Singh, Rakesh Kumar (Frontiers in Pharmacology, 2022)
Parkinson's Disease (PD) is the second most common progressive neurodegenerative disease that is diagnosed mainly based on clinical symptoms caused by the loss of nigrostriatal dopaminergic neurons. Although currently available pharmacological therapies can reduce some of the symptoms, the disease continues to progress, eventually leading to severe motor and cognitive decline and reduced lifespan. The pathology includes hallmark intraneuronal inclusions known as Lewy bodies and Lewy neurites, including fibrillar α-synuclein aggregates. There's also evidence that these aggregates can spread across synaptically connected brain regions, which could explain the disease's progressive character and the emergence of new symptoms over time. The level of α -synuclein is thought to be important in its fibrillization and aggregation. Nucleic acid therapeutics have recently been shown to be effective in treating several severe neurological diseases, raising the possibility of developing innovative molecular therapies for Parkinson's Disease. In this review, we describe advancements in genetic dysregulations in PD and approaches involved in genetic regulation that disease-modifying strategies focus on downregulating α-synuclein gene using various new techniques, notably antisense oligonucleotides, microRNA, short interfering RNA, short hairpin RNAs, DNA aptamers, and gene therapy of vector- assisted delivery system-based therapeutics to target critical elements in the PD. In addition, the current status of preclinical and clinical data-based therapeutics strategies is also reviewed. In this review, we cover these numerous techniques that are still experimental, as well as the hurdles and opportunities of nucleic acid-based therapies for PD.